Cultivar mixtures: a meta-analysis of the effect of intraspecific diversity on crop yield - Reiss, Emily R.; Drinkwater, Laurie E. (Ecological applications, 2018)
Extensive research has shown that greater plant community diversity leads to higher levels of productivity and other ecosystem services, and such increased diversity has been suggested as a way to improve yield and agricultural sustainability. Increasing intraspecific diversity with cultivar mixtures is one way to increase diversity in agricultural systems. We examined the relationship between intraspecific diversity and yield in cultivar mixtures using a meta-analysis of 91 studies and >3,600 observations. Additionally, we investigated how environmental and management factors might influence this relationship, and if the yield stability of cultivar mixtures differed from that of monocultures. We found that the yield increased by 2.2% overall in cultivar mixtures relative to their monoculture components. Mixtures with more cultivars and those with more functional trait diversity showed higher relative yields. Under biotic stressors, such as disease pressure, and abiotic stressors, such as low levels of soil organic matter and nutrient availability, this diversity effect was stronger, resulting in higher relative yields. Finally, cultivar mixtures generally showed higher yield stability compared to monocultures, especially in response to annual weather variability at a site over time. This practice of mixing cultivars can be integrated into intensified cropping systems where species monocultures dominate, as well as in smallholder cropping systems where low-cost improvements are in demand. Overall, these results suggest that cultivar mixtures are a viable strategy to increase diversity in agroecosystems, promoting increased yield and yield stability, with minimal environmental impact.